Vulnerabilidades socioespaciais e COVID-19 no Triângulo Norte e Triângulo Sul (MG) - Silva, Laira Cristina da (2024)
The Covid-19 pandemic, a disease caused by the new coronavirus SARS-CoV-2, arrived in Brazil in late January 2020 in the city of São Paulo. Between 2020 and 2023, the pandemic had multiple consequences on society. In addition to people becoming sick and dying, it resulted in a need to reflect on how city planning influences people's lifestyles and contributes to the pandemic's spread. The fast growth of cities, caused by urbanization, led to cities without adequate infrastructure, increased inequality, pollution, and a lack of basic sanitation. This, in turn, resulted in the spread of diseases, causing various health crises. Geotechnology has played a role in understanding the relationships between virus spread and existing vulnerabilities in an area. In this way, in a world where technologies are increasingly developed, geotechnologies have come to the forefront, aiding in understanding the spread of the virus in the Triângulo Norte and Sul region. In addition, geotechnologies allow that from the moment it is understood how the pandemic spread over the area and what its relationships and weaknesses are, it can be used by planners, researchers and lawmakers to reflect on new ways of urban planning. The objective of the research is analysing the spread of COVID-19 in the region Triângulo Norte and Triângulo Sul of Minas Gerais, between 2020 and 2022. This involves developing a Deprivation Index based on vulnerabilities and, using computational techniques such as geoprocessing, correlating the Deprivation Index with Covid-19. The methodology includes a literature review, database tabulation, and the collection of records and information to understand the studies outcome. In follow up, statistical analysis and database organization were performed using Microsoft Office Excel. Maps were created using the open-source software QGIS 3.16 Hannover. Subsequently, the diffusion data of Covid-19 and the Deprivation Index were validated through Pearson and Spearman correlation. The obtained results showed the importance of the urban network and the influence of cities not only on the economy but also on the healthcare sector and disease spread. Infrastructure, road networks, and relationships between major cities in the Triângulo Norte and Sul region showed the complexity of dynamics and interactions in the region. The high number of cases partly relates to urban networks formed by city hierarchies and their proximity to other disease hotspots, especially in the state of São Paulo. The Social Deprivation Index, when correlated with Covid-19 cases, showed that the weaknesses, while contributing to the introduction and initial expansion of Covid-19 in the Triângulo Norte and Sul region, were not the sole determinant of dissemination. Urban planning has played and still plays a crucial role in pandemics. Furthermore, the pandemic itself highlighted certain priorities that must take precedence in planning. These include the significance of infrastructure, improvement of quality of life, increased green areas, and accessible public spaces for the population. Enhancing mobility and delivering services in accessible locations to avoid long-distance travel are also crucial considerations, among other factors.